Comparative Analysis Of The Level Of Education Of Employees In The Secretarial Field And The Field Of Apparatus Competency Development On Employee Performance In Bkpsdm Palembang City - Sari, Mayang; Harahap, Lily Rahmawati; Effendy, RY. (Universitas Dehasen Bengkulu, 2024)
This study aims to analyze and compare the effect of education level on employee performance in two work units within the Civil Service and Human Resource Development Agency (BKPSDM), namely the Secretariat Division and the Competency Development Division for Civil Servants. This study uses a quantitative descriptive approach with the Independent Sample t-Test statistical analysis method to test differences between two data groups. Data was collected through employee performance evaluation instruments and information on the highest level of education attained. The test results indicate that there is no significant difference in the educational level of employees in the two divisions (significance values of 0.120 and 0.117 > 0.05), which statistically, the educational levels of employees are relatively comparable. However, there is a significant difference in employee performance between the two fields (significance value 0.000 < 0.05), with employees in the Secretariat Field showing higher performance compared to employees in the Civil Service Competency Development Field. This finding suggests that employee performance is not solely determined by formal education level but is also influenced by other factors such as work experience, motivation, work environment, and organizational leadership. The results of this study are expected to serve as a basis for evaluation and consideration in the development of human resource management policies within the BKPSDM environment.